2020
DOI: 10.1186/s13018-020-02149-9
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance ultrasonography for conservative treatment of femoral shaft fractures in young children

Abstract: Background The treatment for femoral shaft fracture (FSF) depends on the age of the patient. While the Pavlik harness is the first choice for patients under 6 months of age, spica casting is preferred for patients over 6 months and under preschool age. Minimally-invasive surgery using elastic stable intramedullary nails is also used in some cases. Skin traction is another treatment choice for some patients who are not candidates for the above methods. This study aimed to evaluate the feasibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In our work, in comparison with the k -wire group, the surgical-related indicators and elbow function of the Métaizeau group were signally superior. Based on US and arthrography, modified Métaizeau technique visually reduced the impact on children and improved surgical safety in children with radial neck fractures, accelerating the prognostic speed and effect of children [ 20 , 30 ]. In terms of postoperative complications incidence in two groups, the Métaizeau group was also signally superior.…”
Section: Discussionmentioning
confidence: 99%
“…In our work, in comparison with the k -wire group, the surgical-related indicators and elbow function of the Métaizeau group were signally superior. Based on US and arthrography, modified Métaizeau technique visually reduced the impact on children and improved surgical safety in children with radial neck fractures, accelerating the prognostic speed and effect of children [ 20 , 30 ]. In terms of postoperative complications incidence in two groups, the Métaizeau group was also signally superior.…”
Section: Discussionmentioning
confidence: 99%
“…It offers real-time visualization of fractures, evaluation of soft tissue injuries, and can guide interventions, especially in resource-limited settings or pre-hospital care. A study showed that in the pediatric patient population, surveillance ultrasonography can reduce radiation exposure to children with femoral shaft fracture closed reductions without increasing the complication rate [32].…”
Section: Future Directionsmentioning
confidence: 99%
“…Femur: In femoral fractures in infancy treated conservatively with traction, it has been shown that follow-up ultrasound examinations can significantly reduce the number of radiographic examinations [42].…”
Section: Lower Extremitymentioning
confidence: 99%